Population dynamics of endangered species Coenonympha oedippus Fabricius, 1787 (Lepidoptera: Satyridae) on the Ljubljansko barje (Slovenia) - Čelik, Tatjana (Acta entomologica slovenica (Ljubljana), 2004)
The False ringlet (Coenonympha oedippus Fabricius, 1787) is the most threatened European butterfly species. In Slovenia the species lives in extensively managed wet meadows of the Ljubljansko barje and in the vicinity of Grosuplje, as well as in dry scrubby grasslands of the Primorska region. In June and July of 1995 and 1996, we studied the dynamics of the population on the Ljubljansko barje, where one of the last marsh populations of the species are to be found in Slovenia. A mark-release-recapture survey was carried out on study site covering an area of 1.27 ha (1995) and 2.63 ha (1996). Mark-recapture data for each sex were processed separately to estimate population size and density, sex ratio, residence (survival) times and catchability.
Keywords: insekti; Ljubljana Marshes; Ljubljansko barje; metulji; populacijska dinamika; velikost populacije